The quest for an appropriate past in literature, art and architecture - Enenkel, K. A. E.; Ottenheym, Koen (Intersections, 2018)
This volume explores the various strategies by which appropriate pasts were construed in scholarship, literature, art, and architecture in order to create "national", regional, or local identities in late medieval and early modern Europe. Because authority was based on lineage, political and territorial claims were underpinned by historical arguments, either true or otherwise. Literature, scholarship, art, and architecture were pivotal media that were used to give evidence of the impressive old lineage of states, regions, or families. These claims were related not only to classical antiquity but also to other periods that were regarded as antiquities, such as the Middle Ages, especially the chivalric age. The authors of this volume analyse these intriguing early modern constructions of "antiquity" and investigate the ways in which they were applied in political, intellectual and artistic contexts in the period of 1400-1700. Contributors include: Barbara Arciszewska, Bianca De Divitiis, Karl Enenkel, Hubertus Günther, Thomas Haye, Harald Hendrix, Stephan Hoppe, Marc Laureys, Frédérique Lemerle, Coen Maas, Anne-Françoise Morel, Kristoffer Neville, Konrad Ottenheym, Yves Pauwels, Christian Peters, Christoph Pieper, David Rijser, Bernd Roling, Nuno Senos, Paul Smith, Pieter Vlaardingerbroek, and Matthew Walker